Relationship Between Clinics Offering Telemedicine and Population Density in Japan: An Ecological Study - Takashi Kuwayama; Kazuhiko Kotani (Telemedicine Reports)
Background: The number of clinics offering telemedicine in Japan has been increasing. Regional characteristics such as population density and the number of physicians may be associated with the provision of telemedicine. This study investigated the relationship between clinics offering telemedicine and such regional characteristics for each prefecture in Japan. Methods: Data were collected from publicly available information that included the percentage of clinics offering telemedicine (real-time synchronous type) among all clinics (in 2022), population density, and the number of physicians for each of Japan's 47 prefectures. An ecological study was carried out to determine the correlation between the percentage of clinics offering telemedicine and regional characteristics for each prefecture, and Pearson correlation analysis and multiple regression analysis adjusted for regional characteristics were performed. Results: The min–max and mean levels were, respectively, 3.4–39.2% and 15.6% of clinics offering telemedicine, 66.6–6402.6 and 657.1 people per square kilometer of population density, and 185.2–356.7 and 274.0 physicians per 100,000 people. Geographically, the northeastern regions appeared to show a high percentage of clinics offering telemedicine relative to the southwestern regions. There was a significant negative correlation between the percentage of clinics offering telemedicine and population density (r = −0.31, p < 0.05; β = −0.31, p < 0.05). Discussion: The negative relationship of the provision of telemedicine in clinics with population density throughout Japan might be a reflection to ensure residents' access to clinics in less populated areas. Although further detailed studies are needed to confirm this, population density might be a useful measure for considering whether to offer telemedicine in clinics in Japan.